PENGARUH PEMBERIAN TEPUNG DAUN KELOR (Moringa oleifera Lamk.) TERHADAP PERTUMBUHAN IKAN NILA (Oreochromis niloticus Linn.) - Indriani, Irma; Hidayat, Saleh (Faculty of Mathematics and Natural Science, Universitas PGRI Palembang, 2011)
ABSTRACTThe research was backed by the amount of protein content in wheat leaves of Moringa (M. oleifera Lamk.) is 27.10 grams and moringa leaf is also a kind of plant that can be a source of protein for growing cattle feed, including one of which is the tilapia (O. niloticus Linn.) . Provision of moringa leaf powder in the formula feed can be integrated with other raw materials, namely rebon flour, fine bran, and wheat flour. The results showed that the using of Moringa leaf powder in the feed formula is veryreal effect on the growth of length and weight of tilapia (O. niloticus Linn.).Key words: Feed, moringa leaf powder, the growth of tilapia (O. niloticus Linn.)